(untitled) (Global Journal of Medical Research, 2021)
Rett syndrome, a neurodevelopmental disorder is caused by MECP2 gene mutations inherited sporadically or x linked dominant fashion. It almost exclusively affects girls. Genetic testing can help in preventing recurrence by offering prenatal diagnosis in affected families. We discuss the case of a patient who had such a mutation and discuss her pregnancy outcomes.